Observations of debris flows at Chalk Cliffs, Colorado, USA: Part 1, In situ measurements of flow dynamics, tracer particle movement and video imagery from the summer of 2009 - McCoy, S.W.; Coe, J.A.; Kean, J.W.; Tucker, G.E.; Staley, D.M.; Wasklewicz, T.A. (Italian journal of engineering geology and environment, 2011)
<span data-sheets-value=""1":2,"2":"Debris flows initiated by surface-water runoff during short duration, moderate-to high-intensity rainfall are common in steep, rocky, and sparsely vegetated terrain. Yet large uncertainties remain about the potential for a flow to grow through entrainment of loose debris, which make formulation of accurate mechanical models of debris- flow routing dif cult. Using a combination of in situ measurements of debris-flow dynamics, video imagery, tracer rocks implanted with passive integrated transponders (PIT) and pre- and post-flow 2-cm resolution digital terrain models (terrain data presented in a companion paper by staley et alii, 2011), we investigated the entrainment and transport response of debris flows at Chalk Cliffs, CO, USA. Four monitored events during the summer of 2009 all initiated from surface-water runoff, generally less than an hour after the first measurable rain. Despite reach-scale morphology that remained relatively constant, the four flow events displayed a range of responses, from long-runout flows that entrained significant amounts of channel sediment and dammed the main-stem river, to smaller, short-runout flows that were primarily depositional in the upper basin. Tracer-rock travel-distance distributions for these events were bimodal; particles either remained immobile or they travelled the entire length of the catchment.The long-runout, large-entrainment flow differed from the other smaller flows by the following controlling factors: peak 10-minute rain intensity; duration of significant flow in the channel; and to a lesser extent, peak surge depth and velocity. Our growing database of natural debris-flow events can be used to develop linkages between observed debris-flow transport and entrainment responses and the controlling rainstorm characteristics and flow properties."" data-sheets-userformat=""2":13057,"3":"1":0,"11":0,"12":0,"15":"Arial","16":10">Debris flows initiated by surface-water runoff during short duration, moderate-to high-intensity rainfall are common in steep, rocky, and sparsely vegetated terrain. Yet large uncertainties remain about the potential for a flow to grow through entrainment of loose debris, which make formulation of accurate mechanical models of debris- flow routing dif cult. Using a combination of in situ measurements of debris-flow dynamics, video imagery, tracer rocks implanted with passive integrated transponders (PIT) and pre- and post-flow 2-cm resolution digital terrain models (terrain data presented in a companion paper by staley et alii, 2011), we investigated the entrainment and transport response of debris flows at Chalk Cliffs, CO, USA. Four monitored events during the summer of 2009 all initiated from surface-water runoff, generally less than an hour after the first measurable rain. Despite reach-scale morphology that remained relatively constant, the four flow events displayed a range of responses, from long-runout flows that entrained significant amounts of channel sediment and dammed the main-stem river, to smaller, short-runout flows that were primarily depositional in the upper basin. Tracer-rock travel-distance distributions for these events were bimodal; particles either remained immobile or they travelled the entire length of the catchment.The long-runout, large-entrainment flow differed from the other smaller flows by the following controlling factors: peak 10-minute rain intensity; duration of significant flow in the channel; and to a lesser extent, peak surge depth and velocity. Our growing database of natural debris-flow events can be used to develop linkages between observed debris-flow transport and entrainment responses and the controlling rainstorm characteristics and flow properties.